PENGARUH HARGA, KUALITAS PRODUK, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE OPPO DI AREA INTERNATIONAL PLAZA PALEMBANG - Yasmina Martini (Fakultas Ekonomi Universitas Tridinanti Palembang, 2016)
This study basically discusses on the influence of price, quality products and promotion toward OPPO Smartphone consumers’ purchasing decision at International Plaza area in Palembang. The population of the study were consumers of Oppo Electronic Indonesia Ltd. International Plaza branch in Palembang. The sample of this study were 60 consumers using the technique of non-probability sampling. There are significant research results price, quality products and promotions simultaneously toward OPPO Smartphone consumers’ purchasing decision at International Plaza area in Palembang with sig F 0,000 <α (0.05). Multiple linear regression equation y = 6.716 + 0.778 X1 + 0.238 X2 - X3 + e 0.331. The independent variables go hand in hand with the dependent variable means that the higher price, product quality and the higher the Promotional Product Purchasing Decisions of Smartphone OPPO Area International Plaza Palembang. There is the influence of price, quality products and promotions partially (alone) toward OPPO Smartphone consumers’ purchasing decision at International Plaza area in Palembang. Correlation (R) of 0.821 has the sole means to show a very strong relationship and be positive (unidirectional). The determination coefficient R Square of 0.674 or 67.4%. Variable Price, Quality Products and Promotions can be explained or there are significant variables Purchase Decision while the remaining 32.6% influenced by other factors not examined.Keywords: Purchase Decision, Price, Quality Products and Promotions